A Comparison of Force Production in Eccentric Hamstring Exercises - Levi Walsh; Joey O'Brien; Declan Browne (International Universities Strength and Conditioning Association, 2024)
Eccentric hamstring training has been identified as a factor in reducing the likelihood of hamstring strain injury (HSI) and improving sport performance. Currently the Nordic hamstring exercise (NHE) is one of the most commonly prescribed exercises for this type of training. However, their effectiveness is blunted as a result of poor compliance rates among athletes, due to a multitude of factors. This study aimed to investigate the effectiveness of the eccentric razor curl exercise (RCE) as an alternative to the NHE for eccentric hamstring training. Twelve amateur rugby players took part in this study, testing their peak eccentric force during both the NHE and RCE. Additionally, soreness induced by each exercise was measured in this study. Significance was set at p ≤ 0.05. The RCE (362.69 ± 45.86 N) resulted in greater force production than the NHE (307.33 ± 67.75 N) (p < 0.001). The RCE also showed lower soreness ratings than the NHE (3.83 ± 1.59 vs 5.67 ± 1.30, p < 0.05). Large effect sizes were shown between the two exercises for soreness ratings (r = 0.71) and force outputs (g = 1.26). The RCE tested significantly better in terms of force and soreness when compared to the NHE in this study. This suggests that the RCE may provide greater benefit to those seeking to optimise their eccentric hamstring training, with greater force and a potential to improve exercise compliance.